2018
DOI: 10.1371/journal.pone.0193261
|View full text |Cite
|
Sign up to set email alerts
|

Dietary cyanogen exposure and early child neurodevelopment: An observational study from the Democratic Republic of Congo

Abstract: BackgroundDietary cyanogen exposure from ingesting bitter (toxic) cassava as a main source of food in sub-Saharan Africa is related to neurological impairments in sub-Saharan Africa. We explored possible association with early child neurodevelopmental outcomes.MethodsWe undertook a cross-sectional neurodevelopmental assessment of 12–48 month-old children using the Mullen Scale of Early Learning (MSEL) and the Gensini Gavito Scale (GGS). We used the Hopkins Symptoms Checklist-10 (HSCL-10) and Goldberg Depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 32 publications
(42 reference statements)
1
25
4
Order By: Relevance
“…More recently, we showed that subjects affected by the disease also have poor neurodevelopmental trajectories including decline in motor and cognitive performances while still relying on improperly processed cassava as the main source of food (Boivin et al, 2017). Our most recent work has extended these findings to children as young as one year of age, suggesting that cassava-associated neurotoxicity may begin when children are weaned from breast milk to cassava porridge (Kashala-Abotnes et al, 2018). In documenting neurocognitive impairments in children with Konzo, Boivin and colleagues also noted sub-clinical symptoms even in Konzo-free children living in Konzo-affected households.…”
Section: Neurological and Clinical Featuresmentioning
confidence: 81%
See 1 more Smart Citation
“…More recently, we showed that subjects affected by the disease also have poor neurodevelopmental trajectories including decline in motor and cognitive performances while still relying on improperly processed cassava as the main source of food (Boivin et al, 2017). Our most recent work has extended these findings to children as young as one year of age, suggesting that cassava-associated neurotoxicity may begin when children are weaned from breast milk to cassava porridge (Kashala-Abotnes et al, 2018). In documenting neurocognitive impairments in children with Konzo, Boivin and colleagues also noted sub-clinical symptoms even in Konzo-free children living in Konzo-affected households.…”
Section: Neurological and Clinical Featuresmentioning
confidence: 81%
“…Samples of cassava flour and urines in a study of very young children had similar concentrations. The cyanogen content in cassava flour was above the safe limit of 10 ppm (Organization FaAOWH, 2018) and the level of SCN urinary excretion was above 350 μmole/litre in most households (Kashala-Abotnes et al, 2018). The introduction of a new food-processing method has helped reduce the cyanogenic content of cassava and hence, the levels of exposure to its cyanogenic compounds, and a subsequent decrease in the number of incident cases of Konzo was noted in select areas of DRC and Tanzania (Mlingi et al, 2011; Banea et al, 2013, 2014; Banea et al, 2012).…”
Section: On the Biomarkers And Mechanisms Of Food (Cassava) Cyanide-amentioning
confidence: 99%
“…Of note, in many countries, children are exposed to naturally occurring compounds containing CN, present in their food, such as in apricot kernels (Chaouali et al, 2013;Cigolini et al, 2011;Gerivani et al, 2016;Kupper et al, 2008;Sauer et al, 2015;Vlad et al, 2015) or cassava (Ariffin et al, 1992). Ingestion of CN contained in the cassava plant has been linked not only to dreadful outbreaks of spastic paralysis with myoclonus in tropical regions of Africa in adults (Tagwireyi et al, 2016), but also to death (Ariffin et al, 1992) and developmental deficits (Kashala-Abotnes et al, 2018) during acute exposure in children.…”
Section: Discussionmentioning
confidence: 99%
“…Kahemba is a rural area of the Kwango region in DRC, which is severely affected by konzo. Konzo is a neurological disease associated with chronic dietary reliance on foodstuffs from insufficiently processed bitter cassava [5]. Cassava cultivars (varieties) are classified as sweets and bitters cassava.…”
Section: Introductionmentioning
confidence: 99%